Antithrombotic therapy for chronic ischemic heart disease: how to balance risk and benefit in different categories of patients? - N. B. Perepech (Атеротромбоз, 2020)
The review focuses on current guidelines for the use of medications that affect hemostasis in the treatment of patients with chronic ischemic heart disease (IHD). The review shows the important impact of negative outcomes of IHD on mortality from cardiovascular system diseases in the Russian Federation. The results of the most significant randomised clinical trials, which assessed the efficacy and safety of various antithrombotic therapy options in patients with various clinical manifestations of IHD, as well as methodological methods for individual assessment of ischemic and hemorrhagic risks, were discussed. Theoretically, the use of anticoagulants in combination with antithrombocytic drugs to reduce the risk of atherothrombotic complications in the phase of the stable course of the IHD is justified. The results of the COMPASS study, which proved the positive effect oflow-dose addition of rivaroxaban to acetylsalicylic acid on the risk of cardiovascular events, cardiovascular death and death from all causes in patients with chronic IHD with maintained sinus rhythm, are reviewed in detail. Discussions were held on how to determine the optimal duration of double antithrombocytic therapy in patients with IHD after percutaneous coronary intervention (PCI), taking into account individual values of ischemic and hemorrhagic risks. Long-term antithrombotic therapy schemes for patients with chronic IHD and atrial fibrillation (AF) that have not been exposed to PCI are presented, as well as current recommendations on how to choose the best antithrombotic therapy scheme for patients with IHD that have been exposed to PCI depending on the risk of stent thrombosis and the risk of bleeding. It has been substantiated that active differentiated antithrombotic therapy should be widely used in everyday practice, which, provided that ischemic and hemorrhagic risks are adequately assessed, creates a real prospect of reducing mortality from IHD and circulatory system diseases in general.